Advancing biliary tract malignancy treatment: emerging frontiers in cell-based therapies - Ao, Jianyang; Hu, Mingtai; Wang, Jinghan; Jiang, Xiaoqing (Frontiers in Immunology, 2025)
Biliary tract malignancies, including intrahepatic cholangiocarcinoma, extrahepatic cholangiocarcinoma, and gallbladder cancer, represent a group of aggressive cancers with poor prognosis due to late-stage diagnosis, limited treatment options, and resistance to conventional therapies like chemotherapy and radiotherapy. These challenges emphasize the urgent need for innovative therapeutic approaches. In recent years, cell-based therapies have emerged as a promising avenue, offering potential solutions through immune modulation, genetic engineering, and targeted intervention in the tumor microenvironment. This Mini-review provides an overview of current advancements in cell-based therapies for biliary malignancies, encompassing immune cell-based strategies such as CAR-T cells, NK cells, dendritic cell vaccines, and tumor-infiltrating lymphocytes. We also examine strategies to overcome the immunosuppressive tumor microenvironment and discuss the integration of cell therapies into multimodal treatment regimens. By synthesizing preclinical and clinical findings, this review highlights key insights and future directions, aiming to assist researchers and clinicians in translating these approaches into effective treatments. The transformative potential of cell-based therapies discussed here makes this review a valuable resource for advancing biliary malignancy research and clinical applications.